Computational eco‐systems biology in Tara Oceans: translating data into knowledge - Shinichi Sunagawa; Eric Karsenti; Chris Bowler; Peer Bork (Molecular Systems Biology)
Graphical Abstract The computational analysis of the data collected by Tara Oceans represents a formidable challenge that will push the boundaries of our understanding of ecosystems at a planetary scale.